Plot size and number of replicates for ryegrass experiments sowed in rows - Marcos Toebe; Alberto Cargnelutti Filho; Cirineu Tolfo Bandeira; Francieli de Lima Tartaglia; Juliana Oliveira de Carvalho; Alessandra Ferreira Cortes; Edgar Salis Brasil Neto (Pesquisa Agropecuária Brasileira, 2022)
Abstract The objective of this work was to determine the optimal plot size and the number of replicates for the evaluation of the fresh weight of ryegrass sowed in rows. Seventy uniformity trials were performed with 'Barjumbo' ryegrass, in 16 basic experimental units (BEUs) of 0.51 m2 each. The fresh weight of ryegrass in the BEUs of 18, 18, 6, 6, and 22 uniformity trials was determined, respectively, at 130, 131, 133, 134, and 137 days after sowing. The optimal plot size was determined through the method of the maximum curvature of the coefficient of variation. The number of replicates was determined in scenarios formed by combinations of treatments and differences between means to be detected as significant by Tukey’s test, at 5% probabilit y. The optimal plot size ranged from 1.73 to 3.18 m2, and the variation coefficient in the optimal plot size from 7.58 to 13.96%. The number of replicates varied from 3.95 (~4) to 32.27 (~33), depending on the experimental design, the number of treatments, and the adopted minimum difference. The optimal plot size is 2.29 m2, and, in experiments with up to 50 treatments, eight replicates are required to identify as significant the differences between treatment means of 20.24%.